Maternal Nitrate and Nitrite Intakes during Pregnancy and Risk of Islet Autoimmunity and Type 1 Diabetes: The DIPP Cohort Study. Issue 11 (28th August 2020) - Mattila, Markus; Niinistö, Sari; Takkinen, Hanna-Mari; Tapanainen, Heli; Reinivuo, Heli; Åkerlund, Mari; Suomi, Johanna; Ahonen, Suvi; Ilonen, Jorma; Toppari, Jorma; Knip, Mikael; Veijola, Riitta; et al.
ABSTRACT: Background: High dietary intake of nitrate and nitrite might increase the risk of type 1 diabetes. To our knowledge, no earlier prospective study has explored whether maternal dietary intake of nitrate and nitrite during pregnancy is associated with the risk of type 1 diabetes in the offspring. Objective: Our aim was to study association between maternal intake of nitrate and nitrite during pregnancy and the risk of islet autoimmunity and type 1 diabetes in the offspring. Design: Children born between 1997 and 2004 at Oulu and Tampere University Hospitals in Finland and carrying increased human leukocyte antigen (HLA)–conferred risk for type 1 diabetes were followed in the Type 1 Diabetes Prediction and Prevention (DIPP) study from 3 mo of age. Islet autoantibodies were screened at 3- to 12-mo intervals from serum samples. Of 4879 children, 312 developed islet autoimmunity and 178 developed type 1 diabetes during a 15-y follow-up. Maternal intake of nitrate and nitrite during the eighth month of pregnancy was assessed after birth using a validated self-administered FFQ. Cox proportional hazards regression was used for the statistical analyses. Results: Maternal intake of nitrate and nitrite during pregnancy was not associated with the child's risk of islet autoimmunity [nitrate: HR 0.99 (95% CI: 0.88, 1.11); nitrite: HR 1.03 (95% CI: 0.92, 1.15)] or type 1 diabetes [nitrate: HR 1.02 (95% CI: 0.88, 1.17); nitrite: HR 0.97 (95% CI: 0.83, 1.12)] when adjusted for energy (residual method), sex, HLA risk group, and family history of diabetes. Further adjustment for dietary antioxidants (vitamin C, vitamin E, and selenium) did not change the results. Conclusion: Maternal dietary intake of nitrate or nitrite during pregnancy is not associated with the risk of islet autoimmunity or type 1 diabetes in the offspring genetically at risk for type 1 diabetes.